Our duties in talent management in the light of the results of the International Hungarian Mathematics Competition of 2017 - Erika Roman; Роман Еріка; Román Erika; Fried Katalin (University of Debrecen, 2018)
Abstract. The 4th International Hungarian Mathematics Competition held in Transcarpathia, Beregszász between April 28 and May 1, 2017, was organized by the Hungarian Carpathian Hungarian Teachers' Association (KMPSZ) and the Ferenc Rákóczi II. Transcarpathian Hungarian Institute (II. RFKMF). The venue for the competition was the building of the Ferenc Rákóczi II. Transcarpathian Hungarian Institute. 175 Hungarian students from Hungary, Romania, Slovakia, Serbia and Ukrain participated. In the first part of this article, we are going to deal with the problems given in the two rounds to students in grades 5 and 6.

A IV. Nemzetközi Magyar Matematika Versenyt 2017. április 28. és május 1. között a Kárpátaljai Magyar Pedagógusszövetség (KMPSZ) és a II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola rendezte Kárpátalján, Beregszászban. A verseny helyszíne a II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola épülete volt. A versenyen 175 magyarországi, romániai, szlovákiai, szerbiai és ukrajnai magyar származású diák vett részt. Ebben a cikkben az 5. és 6. osztályosok I. és II. fordulójának feladataival foglalkozunk.
https://tmcs.math.unideb.hu/load_doc.php?p=328&t=doc
Keywords: problem solving; achievement control; copmpetition preparation; problémamegoldás; teljesítmény ellenőrzés; verseny felkészítés